2008
DOI: 10.1128/aem.01592-08
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in the Ectomycorrhizal Community in Two Soil Horizons of a Temperate Oak Forest

Abstract: The species structure of an ectomycorrhizal (ECM) community was assessed monthly for 15 months in the two horizons (A1 and A2) of an oak temperate forest in northeastern France. Ectomycorrhizal species were identified each month by internal transcribed spacer sequencing. Seventy-five fungal symbionts were identified. The community was dominated by Tomentellaceae, Russulaceae, Cortinariaceae, and Boletales. Four species are abundant in the study site: Lactarius quietus, Tomentella sublilacina, Cenococcum geophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 63 publications
14
105
1
2
Order By: Relevance
“…In contrast, the very abundant C. geophilum had no significant difference in occurrence in the Oi + Oe and Oa layers. This distribution has been shown in a number of studies (Baier et al 2006;Courty et al 2008) where the medium distance exploration types (L. rufus, C. neofurvolaesus, and C. delibutus) occur more often in the loose substrate horizons (Oi + Oe) than the more compact Oa layers. However, the short distance exploration type T. fibrillosa was also found preferentially in the Oi + Oe layer, suggesting that factors other than the compactness of the soil substrate may also be important, such as tolerance to fluctuations in soil temperature and moisture (Baier et al 2006).…”
Section: Distribution and Diversity Of Mycorrhizasmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, the very abundant C. geophilum had no significant difference in occurrence in the Oi + Oe and Oa layers. This distribution has been shown in a number of studies (Baier et al 2006;Courty et al 2008) where the medium distance exploration types (L. rufus, C. neofurvolaesus, and C. delibutus) occur more often in the loose substrate horizons (Oi + Oe) than the more compact Oa layers. However, the short distance exploration type T. fibrillosa was also found preferentially in the Oi + Oe layer, suggesting that factors other than the compactness of the soil substrate may also be important, such as tolerance to fluctuations in soil temperature and moisture (Baier et al 2006).…”
Section: Distribution and Diversity Of Mycorrhizasmentioning
confidence: 57%
“…Ectomycorrhizas can enhance K uptake and storage in roots by increasing the size of vacuolar pools and through increasing K influx rates and decreasing K efflux rates (Rygiewicz and Bledsoe 1984). In natural ecosystems, the fine roots of most trees are colonized by a large number of ectomycorrhizal fungal species (Erland and Taylor 1999;Courty et al 2008). Such investigations have shown that ectomycorrhizal communities in forests can be highly diverse, but these communities tend to be dominated by a few species and have a high number of rare species (Erland and Taylor 1999;Courty et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to: (a) propitious weather conditions favour fruiting and the germinated spores colonise fine roots and form new ectomycorrhizas; and (b) the main shift in the relative abundance of T. melanosporum ectomycorrhizas from year to year occurs in autumn, when they have one of their two seasonal peaks (Bonet et al 2001), whereas the sampling has been performed in spring. The seasonal patterns of EM populations differ across species (Courty et al 2008) and our results indicate that the influence of weather is morphotype-specific. This could also contribute to changing the relative abundance of T. melanosporum ectomycorrhizas from one season to another.…”
Section: Em Community Of the Truffle Treementioning
confidence: 62%
“…Since the EM fungi differ in their preference for soil depth (Courty et al 2008), the EM community is likely to differ from that in wild truffières. In addition, the abundance of T. melanosporum ectomycorrhizas in our study is lower than generally reported in truffle plantations (which are usually established with nursery-inoculated seedlings on agricultural soils), and the richness of soil-borne EM fungi is higher (Sánchez-Durán et al 2009;Águeda et al, 2010).…”
Section: Temporal Evolution After the Canopy Openingmentioning
confidence: 99%